Energy, Fat, Carbohydrate Adequacy, Physical Activity: Relation to Nutrition Students' Body Fat Percentage - Fila Rachmad Ramadan; Lini Anisfatus Sholihah; Noor Rohmah Mayasari; Wildan Alfira Gusrianto (Poltekkes Kemenkes Surabaya, 2024)
Obesity is caused by excessive fat accumulation due to high energy, carbohydrate, fat intake, and low physical activity, leading to serious health risks. This study examines the relationship between the adequacy levels of energy, fat, carbohydrates, and physical activity with body fat percentage in nutrition students at Universitas Negeri Surabaya. This research used a quantitative method with a cross-sectional design involving 111 respondents selected through cluster random sampling based on student cohorts. Data were collected using a 3x24-hour Food Record questionnaire and the IPAQ Short Form to assess physical activity levels, and body fat percentage was measured using BIA. The results showed that most respondents had a deficit in energy adequacy (72.1%) and carbohydrate adequacy (91%), 57.6% had adequate or higher fat intake, and 64% were physically active. Statistical analysis showed a significant relationship between energy adequacy levels (p=0.024; OR=4.4) and fat adequacy (p=0.000; OR=6) with body fat percentage, as well as a significant relationship between physical activity (p=0.028; OR=2.3) and body fat percentage. No significant relationship was found between carbohydrate adequacy levels and body fat percentage (p=0.316). This study highlights the importance of maintaining balanced energy and fat intake and increasing physical activity to control body fat percentage and prevent obesity among female students. Nutrition and physical activity intervention programs tailored to the needs of female students are necessary to achieve optimal body health.